Influenza vaccine effectiveness 2010-11 in Portugal obtained by two methods: results from the EuroEVA study - Machado, Ausenda (2011)
Background: Every year the influenza vaccine is reformulated so estimating the influenza vaccine effectiveness (VE) every season and in an early stage is important to support public health decisions. Since 2008, Portugal has been participating in the I-MOVE (Influenza Monitoring Vaccine Effectiveness in Europe) project with the EuroEVA study, which main objective is to estimate seasonal and pandemic vaccine effectiveness during and after the influenza season. In this context, we used two methods to estimate VE for the 2010-11 seasonal influenza vaccine, both in the elderly and in all age groups. Methods: Two approaches were used to estimate VE: the Test Negative Design (TND) and the Screnning method (SM). For TND, laboratory-confirmed influenza cases (ILI+) were compared to laboratory-negative influenza ILI patients (ILI-). ILI cases were selected by general practitioners using systematic sampling. For SM, the vaccine coverage (VC) on the ILI+ cases (recruited from the TND) was compared to the VC estimated in the general population using a telephone survey (ECOS). Results: Overall results obtained by the EuroEVA study indicate that crude 2010-11 seasonal VE estimate was 79% (CI95% 43-94) and 70% (CI95% 32-87) for the TND and SM, respectively. After adjustment, the respective VE estimates decreased: 58 (CI95% -61-89) and 64% (CI95% 17-84). Conclusions: VE point estimates obtained by the two methods were very similar and an explanation for this consistency could be that the seasonal vaccine coverage estimates between ILI- (17.4%) and the population based telephone survey (17.5%) were also very close. Nevertheless, and due to small sample size, our study was unable to estimate VE for specific seasonal vaccine target groups. Further efforts should be done to increase sample size, mainly in the elderly population.